Impact of Random Pointing Errors on Coherent Laser Radar Efficiency and Scintillation Index: A Theoretical Overview - Philip Gatt; Scott M. Shald (Newest Updates in Physical Science Research Vol. 11, 2021)
The target size plays a key role. When operating against an essentially infinitely wide target, the transmitter and receiver are never misaligned with the target regardless of the size of the pointing error. In this analysis we assume matched elliptical Gaussian transmit, ‘t’ and BPLO, ‘b’ with \(e^-2\) irradiance radii, \(ω_x\) and \(ω_y\) along the x and y axes. We also assume an elliptical diffuse Gaussian target, f‘ T’, centered at the origin, with peak power reflectance function \(ρ_π0\) (sr), \(e^-2\) radii \(ω_Tx\) and \(ω_Ty\). The formulas given here may assist in deriving tolerances when designing new coherent ladar systems. The lessons learned from examining Gaussian beam ladar are likely to help in designing better sensors and understanding existing system behavior.